Rumah Ramah Apps: Supporting English Learning for Low Vision Students in Higher Education - Hamid, Sitti Maryam; Rum, Eka Prabawati; Mannong, Andi Bulkis Maghfirah; Syam, Ummi Khaerati; Sangkala, Ismail (INTERACTION: Jurnal Pendidikan Bahasa, 2023)
This research aims to elaborate the use Rumah Ramah Apps by English teachers for low vision student in supporting English learning. The data was obtained through in-depth interviews with five lecturers who and a low vision student who implemented rumahramah.id Apps in English language teaching and learning.The research method adopted in this research is Research and Development (R&D). The findings of the study revealed that (1) Developing English language learning services through the 'Rumah Ramah' application for 'Low Vision' students at Universitas Muhammadiyah Makassar focused on activities ranging from signing in to the Rumah Ramah page to comprehending the use of features on the instructor dashboard and course dashboard to the process of entering learning material, which focuses on general and content drip settings. (2) Implementing English language learning services through the 'Rumah Ramah' Apps for 'Low Vision' students at Universitas Muhammadiyah Makassar focused on the way to access Rumah Ramah Apps and utilize of Rumah Ramah Apps for low vision student. As a result, Rumah Ramah is extremely practicable for usage as an English learning media in assisting lecturers in designing material for low vision students.